AB1080 Neurological evaluation of childhood-onset cryopyrin-asscociated periodic syndromes-a preliminary report. (12th June 2018) - Kilic, H.; Sahin, S.; Duman, C.; Adrovic, A.; Barut, K.; Kasapcopur, O.; Saltik, S.
Abstract : Background: The cryopyrin-associated periodic syndrome (CAPS) is a treatable autoinflammatory disease that encompasses familial cold autoinflammatory syndrome(FCAS), Muckle–Wells syndrome(MWS), and chronic infantile, neurologic, cutaneous, and articular syndrome (CINCA), which are quite different in severity. Early diagnosis of CAPS and prompt initiation of IL-1 blockers have significant effect on the neurologic prognosis of CAPS. Although neurologic complications of CINCA are well-known, there are scarce date regarding neurologic features of milder phenotypes. Objectives: We aimed to review the neurologic features in detail and summarise the other CAPS-related manifestations in 9 children. Methods: All children with CAPS that have been followed-up from paediatric rheumatology outpatient clinic, were enrolled to the study. In addition to the neurologic examination, magnetic resonance imaging (MRI) of brain, electroencephalography, eye examination, hearing test and neuropsychiatric tests were done. Demographic, clinical features, genetic analysis and laboratory tests were noted from patient records and hospital database. Results: The median age of the subjects was 6 years (range 2–14 years), with a female-to-male ratio 4/5. Most frequently noted neurologic clinical manifestations during the disease course were papilledema (3/9) and epilepsy (3/9), followed by neurodevelopmental delay (2/9), aseptic meningitis (2/9), upper motor neuron findings (2/9), ocular symptoms/signs (2/9), sensorineural hearing loss (1/9), optic atrophy (1/9) (table 1). MRI of the brain was abnormal in two patients. Conclusions: Increased understanding and awareness of this rare but treatable syndrome among neurologists is essential, since the disease could manifest with neurologic manifestations such as seizure, papilledema, sensorineural deafness and aseptic meningitis. If remains untreated and recognised, this autoinflammatory syndrome could lead to significant morbidity and mortality. Hence, early treatment with anti-interleukin-1 therapy provides complete resolution of symptoms and, also prevent progression of neurologic findings when initiated in the late stage of the disease. Reference: [1] Eroglu FK, Kasapcopur O, Beşbaş N, et al. Genetic and clinical features of cryopyrin-associated periodic syndromes in Turkish children. Clin Exp Rheumatol;34: 115–120. Disclosure of Interest: None declared